0073 Optogenetic Control Of Sleep Slow Waves To Improve Recovery After Ischemic Stroke. (27th April 2018) - Facchin, L; Schöne, C; Mensen, A; Bandarabadi, M; Schindler, K; Adamantidis, A; Bassetti, C
Abstract: Introduction: Experimental studies suggested a role for sleep in the reorganization of neuronal connectivity map and brain plasticity during stroke recovery. Here, we investigate the role of Slow Waves (SW) oscillations during sleep on brain plasticity following ischemic stroke using optogenetic tools and in vivo electrophysiology in mice. Methods: Ischemic stroke was caused in wild type mice using middle cerebral artery occlusion (MCAO). SW-like oscillations were induced by optogenetic optical stimulations of ChR2- (activation) or ArchT (silencing)-expressing pyramidal neurons within the peri-lesional primary somatosensory forelimb (S1FL) cortex. Randomly distributed single light pulses were delivered for 2 h sessions from post-stroke day 5, and consecutively every day until post-stroke day 15. The effect of optogenetically evoked SW on motor outcomes was investigated with behavioural tests at post-stroke day 4, 7, 10 and 15. Results: We showed that MCAO induced an increased amount of NREM sleep following ischemic stroke, where ipsilesional SW where longer in duration and wider in amplitude, compared to control animals. We first showed that optogenetic activation (ChR2) and silencing (ArchT) of pyramidal neurons in the per-lesional S1FL cortex successfully induced SW sleep-like responses in ipsilesional and contralesional electroencephalography (EEG) traces that were indistinguishable from spontaneous SW oscillations occurring during NREM sleep. Evoked and spontaneous SW were automatically detected and compared in amplitude, slope and duration. We next showed that chronic optogenetic induction of SW-like, predominantly during NREM sleep, significantly improved the recovery of fine motor movement as compared to control mice. Interestingly, SW post-stroke induction didn't affect the recovery of movement strength or symmetry. Conclusion: Our results further confirmed the essential role of NREM sleep, and SW in particular, in brain plasticity following ischemic stroke. Importantly, we showed that optogenetically-induced SW-like oscillations, targeting the activity of pyramidal neurons within the peri-lesional cortex, significantly improved functional outcomes after stroke. Support (If Any): Swiss National Science Foundation (SNF).